Incidence of Banana Bunchy Top Disease in West Java, Indonesia - Endang Nurhayati (Universitas Gadjah Mada, 2003)
Banana Bunchy Top Disease (BBTD) is the most economically important virus disease of bananas. The disease is widespread in Asia and South Pacific regions. In Indonesia, it was first reported in 1979 in the regency of Bandung in West Java, and now becoming widespread in several growing areas. A survey on disease incidence was conducted in five main banana growing districts in the provinces of West Java and Banten. BBTD was prevalent in four of five main banana growing districts with disease incidence varied from 0 to 38.6%. Most of the local cultivars grown was infected with various level of intensity. Cultivars Muli, Nangka, Raja, Kepok and Ambon were among the cultivars infected. ELISA confirmed that banana bunchy top virus is the causal pathogen and showed the relative susceptibility of the cultivars. Most of growers was not aware of the disease and tended to keep the infected banana. Some growers cut the infected pseudostem, but did not uproot the stem, allowing the disease to develop into the new plantings.